Temporal Dynamics of Motor Functioning and Cognitive Aging - Finkel, Deborah (J Gerontol A Biol Sci Med Sci, 2016)
BACKGROUND. Because of the possible implications for intervention and thus successful aging, researchers have striven to determine whether the age changes in physical and cognitive functioning are coincident or does functioning in one domain change before, and possibly contribute to, functioning in the other. METHODS. Bivariate dual change score models were applied to four cognitive factors and three motor functioning factors available from 813 adults who participated in the Swedish Adoption/Twin Study of Aging. Participants were aged 50–88 at the first of six waves of testing covering a 19-year follow-up period; 68% participated in at least three waves. RESULTS. Model comparisons indicated dynamic coupling relationships between Balance and Fine Motor factors and the Speed cognitive factor. Decline in motor function precedes decline in performance on processing speed tasks, even though the motor function tasks were not timed. Results indicated possible bidirectional coupling between Fine Motor and Speed. CONCLUSIONS. Combined with other dual change score model analyses of cognition and physical function, a picture is beginning to emerge of the cascade of events that may lead to cognitive aging.